Photonic Crystal Waveguide Weakly Interacting with Multiple Off-Channel Resonant Features Formed of Kerr Nonlinear Dielectric Media. (19th April 2007) - McGurn, A. R.
Abstract : A theoretical study is presented of guided modes of a photonic crystal waveguide for cases in which they interact with multiple bound electromagnetic modes localized on off-channel impurity features of Kerr nonlinear media. The interest is on the properties of resonant scattering and optical bistability exhibited by the system and the coherent scattering of the guided modes due to their simultaneous resonant interactions with multiple bound modes. In first study, two off-channel features on opposite sides of a photonic crystal waveguide are made of different Kerr nonlinear dielectric media. In second study, an off-channel feature is composed of two neighboring sites having different Kerr dielectric properties. In addition to numerical results a number of analytical results are presented providing simple explanations of the quantitative behaviors of the systems. A relationship of these systems to forms of electromagnetic-induced transparency and modifications of waveguide dispersion relations is discussed.